2018
DOI: 10.2478/bsrj-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Government Subsidy on Non-Technological Innovation and Firm Performance in the Service Sector: Evidence from Germany

Abstract: Background: To enhance the innovation activities at the firm level, government subsidies plays an important role. Objectives: The objective of the study is to explore whether firms in service sector that receive government subsidies engage more in marketing and organizational innovation activities than their counterparts. Second, focusing on the subsidized firms in the service sector, the impact of innovations (marketing as well as organizational) on firm performance—measured as the probability of submitted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
14
1
1
Order By: Relevance
“…In this case, the lack of a dependent relationship can be explained. Now, regarding the finding itself of an insignificant relationship between innovation subsidy and innovation, this contrasts the existing literature (Basit, Kuhn, & Ahmed, 2018;Guo, Guo, & Jiang, 2016).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In this case, the lack of a dependent relationship can be explained. Now, regarding the finding itself of an insignificant relationship between innovation subsidy and innovation, this contrasts the existing literature (Basit, Kuhn, & Ahmed, 2018;Guo, Guo, & Jiang, 2016).…”
Section: Discussioncontrasting
confidence: 67%
“…In this sense, this variable measures the perception of effectiveness of the subsidy from the SMEs perspective. This variable is validated in the studies of impact of innovation subsidy on innovation (Basit, Kuhn, & Ahmed, 2018;Hall, Lotti, & Mairesse, 2009;López-Acevedo & Tinajero-Bravo, 2013;Yao, Xu, Jiang, & Zhang, 2015).…”
Section: Independent Variablementioning
confidence: 98%
See 1 more Smart Citation
“…Cheng et al carried out research from the perspective of political connection and believed that political connection helps enterprises to obtain tax incentives and government subsidies [36]. Basit et al studied innovation subsidy in service industry and found that enterprises can significantly improve their performance through marketing innovation [37]. Some scholars also paid attention to the problem of corporate fraud for subsidy.…”
Section: Innovation Subsidymentioning
confidence: 99%
“…Así las cosas, los esfuerzos de innovación tecnológica deben ser apoyados por la innovación en marketing y organizativa (González-Blanco, Coca-Pérez y Guisado-González, 2019; Nieves y Diaz-Meneses, 2016; Vrcelj, 2013;Xu, Wu y Ren, 2012). No obstante, los investigadores están descuidando las innovaciones organizativas o en marketing, que son a la par fundamentales para el crecimiento, rendimiento y funcionamiento efectivo (Abdul, Kuhn y Ahmed, 2018;Chung y Kim, 2017;Damanpour, 1991;Damanpour y Evan, 1984). Actualmente, son escasos los estudios sobre las innovaciones enfocadas al marketing (Gunday, Ulusoy, Kilic y Alpkan, 2011;Quaye y Mensah, 2019;Reiner, Reimann y Vitkauskaite, 2016;Zakerian et al, 2017), a pesar de que la innovación en marke-ting como estrategia empresarial permite a las organizacio-nes establecer una relación más estrecha con sus clientes hasta convertirlos en promotores de la propia empresa (Kotler y Keller, 2006).…”
Section: Introductionunclassified